STIR CASTING METHOD ON ALUMINA (Al2O3) COMPOSITE MATRIX WITH SiC STRENGTHEN AND MAGNESIUM (Mg) ADDITION TO MICROSTRUCTURE AND MECHANICAL PROPERTIES - Widodo, Basuki; Wahyu Panji Asmoro; Amirullah Firmansyah (Journal of Sustainable Technology and Applied Science (JSTAS), 2022)
Aluminum is a material that has the ability as a material that is widely used because of its light weight, good corrosion resistance, good appearance, reliable electrical conductor, good electricity conductor, and several other advantages of this material. The development of aluminum (Al) material in the form of aluminum matrix composite (AMC) is often applied in various fields including automotive, industry, military, and aviation. The reinforcing particle that is often used in AMC is silicon sarbide (SiC) to improve the properties of AMC. The addition of magnesium (Mg) is useful as a wetting agent for reinforcing particles and matrices. This study aims to determine the effect of adding magnesium (Mg) on the mechanical properties and microstructure of the aluminum matrix composite 1100 series reinforced with silicon carbide (SiC) using the stir casting method. The reinforcing silicon carbide (SiC) particles were added to the aluminum matrix composite (Al) by 5%. The variations in the addition of magnesium were 0.75%, 1.25%, and 1.75% as wetting agents. To find out the mechanical properties, this research was carried out by testing the tensile strength and hardness. The hardness test results showed the highest hardness in the magnesium (Mg) 1.75% variation of 84.67 HRB and the highest tensile strength in the pure aluminum (Al) variation of 9.41 Kgf/mm2.